Sugar : Micheal Ray Richardson, eighties excess, and the NBA - Rosen, Charles (University of Nebraska Press, 2018)
"Sugar considers aspects of the league's dysfunction in light of basketball's rapidly increasing popularity during the 1970s and 1980s"--